PENGARUH AKTIVITAS FISIK JALAN KAKI TERHADAP KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III - Apriliani, Peti; Putri, Noviyati Rahardjo; Maulina, Rufidah; Novika, Revi Gama Hatta; Nurhidayati , Siti (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND : Sleep disorders are common in pregnant women during the third trimester, with frequent urination being a prevalent issue due to weakened bladder muscles, leading to deteriorated sleep quality. Physical activity, such as walking, is recommended as an easy, effective, and economical way to improve sleep quality in pregnant women. AIMS :  To analyze the effect of walking on sleep quality in third-trimester pregnant women at Kebakkramat I Karanganyar Health Center, Central Java. METHOD : This study used a Quasi-Experimental design with a Pretest-Posttest Control Group approach. The sample consisted of 80 third-trimester pregnant women, selected using Multistage Sampling. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was used to measure sleep quality. The intervention involved walking for 20 minutes over two weeks. RESULT :  The analysis used the Delta score mean test between the pre-tests and post-tests for each respondent to show a significant effect of walking on sleep quality. A negative delta value shows a decrease in the PSQI score, indicating improved sleep quality for the respondent, and vice versa. The intervention group had a lower delta score mean of -3.13 compared to the control group, indicating that walking effectively improves sleep quality. CONCLUSION : Walking has significant potential to improve sleep quality in third-trimester pregnant women. Pregnant women are encouraged to walk regularly and increase their knowledge about pregnancy.